IMPLEMENTASI KONVENSI CEDAW (CONVENTION ON THE ELIMINATION OF ALL FORM OF DISCRIMINATION AGAINST WOMEN) OLEH PEMERINTAH INDONESIA DALAM MENGATASI PERDAGANGAN PEREMPUAN DI INDONESIA TAHUN 2007-2018 - Nur Fatimah Ningrum; M. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The purpose of this research is to explain the general description of human trafficking in Indonesia and the implementation of CEDAW Convention (Convention on the Elimination of All Forms of Discrimination Against Women) and also Indonesian wisdom to resolve of women trafficking. This research method used kualitative research. This research is focused to discuss about the implementation of CEDAW Convention and Indonesian wisdom to resolve of women trafficking. Then,                 This research used the constructivism perspective. The research also used state-level analysis.The research concluded that Indonesia has ratified the CEDAW Convention,  some laws and regulation since the ratification of the convention has been published, Indonesia also establish the task force on prevention and management the victims of human trafficking which meaning to make effective and ensure the implementation and prevention of human trafficking. Other that, the Indonesian Government also has established the National Commission on Violence Against Women (Komnas Perempuan), which is one of the national human rights institutions that focuses on upholding the Indonesian women rights. Some efforts were made by Komnas Perempuan as a form of implementation of the CEDAW Convention to resolve of women trafficking. These efforts include the National Commission on Violence Against Women to give advice and consideration to the government, legislative and judicial institutions, as well as community organizations, women's national commissions use the CEDAW framework as a reference in the implementation of work. Keywords: Implementation, CEDAW Convention, Women Trafficking